(untitled) (Revista de Ciências Agroveterinárias, 2021)
The growth of sugarcane plants is greatly reduced due to the occurrence of drought stress, which ultimately affects production. Therefore, different strategies have been used to attenuate stress conditions, such as the exogenous application of glycine betaine. The objective of this work was to evaluate the growth rate and dry mass of sugarcane that received a glycine betaine application and was submitted to drought stress and rehydration. The experiment was carried out in a greenhouse with six treatments: G0I - plants without glycine betaine with adequate irrigation, G0E - plants without glycine betaine and drought stress, G1I - plants with an application of glycine betaine and adequate irrigation, G1E - plants with an application of glycine betaine and drought stress, G2I - plants with two applications of glycine betaine and adequate irrigation, G2E - plants with two applications of glycine betaine and drought stress. Six days after the stress, the plants were rehydrated. The relative growth rates of sugarcane plants decreased with the drought stress. However, these reductions were partially minimized with the foliar application of glycine betaine, mainly with the rehydration, with the relative growth rate decreasing by only 19% and 18.4%, respectively, in G1 and G2, while the reduction was 37.2% in G0. Glycine betaine also minimized reductions in total dry mass production under drought stress, with decreases of 5.8% and 5.9% in G1 and G2, respectively, while it was 15.1% in G0. The leaf application of glycine betaine improves the relative growth rate of sugarcane plants under drought stress, especially after rehydration, which decreases the negative effects of stress on dry mass production.